2013
DOI: 10.1001/jamasurg.2013.2750
|View full text |Cite
|
Sign up to set email alerts
|

Massachusetts Health Care Reform and Reduced Racial Disparities in Minimally Invasive Surgery

Abstract: Importance Racial disparities in receipt of minimally invasive surgery (MIS) persist in the United States and have been shown to also be associated with a number of driving factors, including insurance status. However, little is known as to how expanding insurance coverage across a population influences disparities in surgical care. Objective To evaluate the impact of Massachusetts health care reform on racial disparities in MIS. Design, Setting, and Participants A retrospective cohort study assessed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 23 publications
3
46
2
Order By: Relevance
“…39 Multiple studies have suggested increased surgical referrals and decreased disparities in the receipt of certain procedures after expanded insurance coverage. [40][41][42][43][44][45] However, our data do contrast another recent study that found no change in disparities of coronary revascularization procedures after Massachusetts health care reform, although their analysis was limited by short follow-up data ending in September of 2008, only nine months after implementation of mandate requiring insurance coverage. 46 The HCUP-SID capture nearly 100% of all inpatient admissions across states but are bound by the limitations of administrative data, including the possibility of coding discrepancies and limited clinical granularity better captured in clinical datasets.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…39 Multiple studies have suggested increased surgical referrals and decreased disparities in the receipt of certain procedures after expanded insurance coverage. [40][41][42][43][44][45] However, our data do contrast another recent study that found no change in disparities of coronary revascularization procedures after Massachusetts health care reform, although their analysis was limited by short follow-up data ending in September of 2008, only nine months after implementation of mandate requiring insurance coverage. 46 The HCUP-SID capture nearly 100% of all inpatient admissions across states but are bound by the limitations of administrative data, including the possibility of coding discrepancies and limited clinical granularity better captured in clinical datasets.…”
Section: Discussioncontrasting
confidence: 99%
“…The designation of revascularization included all open bypass procedures as well as endovascular interventions (ICD-9-CM 00. 40 48). All amputations of bony structures from the level of hip disarticulation through toe amputation were considered an amputation (ICD-9-CM 84.10 -84.18).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…We selected these particular surgical conditions given extensive documentation of disparities in patient presentation with and subsequent care received based on insurance coverage, in addition to data suggesting an association between insurance expansion and care delivery for these conditions. [5][6][7][8][9][10][11][12][13][14] Surgery for appendicitis, cholecystitis, and diverticulitis represent the three most frequent and highest morbidity procedures in general surgery. 20 Vascular diseases, including aortic aneurysm and PAD, are increasingly prevalent in the U.S., and timely appropriate management has been shown to directly impact both mortality and major morbidity.…”
Section: Data Source and Outcomesmentioning
confidence: 99%
“…[13][14][15] However, it is unclear whether the Massachusetts experience generalizes to the ACA's Medicaid expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Expanded coverage was associated with increased access to MIS for racial minorities and historically underinsured patients. 52,53 This suggests that a multipronged approach including enhanced education of patients and providers, and policy changes to improve access and incentivize the use of best practices, may be needed to reduce unjustified variation.…”
Section: Discussionmentioning
confidence: 99%